The Case of Syiqaq in Judges’s Gorontalo Religion Court Perspective - Fauzan Nento; Titin Samsudin (Al-Mizan (e-Journal), 2018)
This study discusses judges' perceptions in the Gorontalo Religious Court regarding the case of syiqaq. This research is a field research with data collection methods such as observation, interviews and documentation. The collected data is processed and analyzed with qualitative descriptive. The results showed that the application of the case of syiqaq in the Religious Courts caused friction of perceptions between Islamic law, marriage law and the Supreme Court Regulations of the Republic of Indonesia, making it controversial in this era. Divorce because syiqaq has the characteristics, which involves two peacemakers from both sides, but in actualization within the Religious Courts institution has changed so that the syiqaq is no longer visible and only becomes one theoretical discourse.